The apprehensions in the graphic registry for the study of the partial derivative - Vigo Ingar, Katia (2019)
The objective of this article is to present an extension of the Duval study in relation to the apprehensions in the graphic register of a function of two variables, to analyze a didactic situation and to investigate the articulations of the apprehensions in the study of the partial derivative. Its relevance in the teaching-learning of the Differential Calculus of two variables is wide, since the information that the graph provides is important for the construction of knowledge of functions of two variables. Our research is qualitative, specifically, aspects of the didactic engineering of Michèle Artigue. It was found that the articulation of the apprehensions in the graphic registry, mediated by the Mathematica software, allowed the students to conjecture properties, apply them in optimization problems and adapt to solve these problems geometrically.